The employment effects of countercyclical public investments - Buchheim, Lukas and Watzinger, Martin (American Economic Journal: Economic Policy)
This paper estimates the causal impact of a sizable German public investment program on employment at the county level. The program focused on improving the energy efficiency of school buildings, making it possible to use the number of schools as an instrument for investments. It also enforced tight deadlines, reducing potential implementation lags. The program was cost-effective, creating, on average, one job for one year for an investment of €24,000. The employment gains are detectable after nine months and are accompanied by an unemployment reduction amounting to half of the job creation. Employment grew predominately in the directly affected industries.- Reproduced